(untitled) (Materiali di Estetica. Terza serie, 2022)
After a short story of the journal «Corrente», founded in 1938 by Ernesto Treccani, the article remembers the role played in it by Vittorio Sereni, who studied at Milan’s University with Antonio Banfi, and looks at his first poetry book, Frontiera, in which ermetic manner coexists with something that can be said realistic. Sereni took also part in 1978 in the establishment of, and participated in its initiatives